2015
DOI: 10.1590/1678-457x.6443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of agro-ecological production areas on antioxidant activity, reducing sugar content, and selected phytonutrients of orange-fleshed sweet potato cultivars

Abstract: Sweet potato is an important staple, and it is mainly known for its contribution of β-carotene in human diet. The effects of cultivar and habitat on this pigment and other nutritional characteristics of the crop still require investigation. In this study, three locally bred cultivars of sweet potato, two of which are orange-fleshed, were grown in three different agro-ecological areas to determine soluble sugar content, β-carotene, and total antioxidants of roots. In addition antioxidant activity, total caroten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
0
7
0
3
Order By: Relevance
“…The contents of polyphenols and the antioxidant activity can be influenced by agro-ecological conditions, including locality, humidity, soil composition, water deficit, and temperature. Motsa et al [36] found that the contents of secondary metabolites, especially of polyphenols, can increase under drought conditions because of the increased oxidative stress perceived. Similarly, Oh et al [37] revealed that drought stress and high temperatures can lead to increased amount of bioactive compounds which may serve as the main defense mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The contents of polyphenols and the antioxidant activity can be influenced by agro-ecological conditions, including locality, humidity, soil composition, water deficit, and temperature. Motsa et al [36] found that the contents of secondary metabolites, especially of polyphenols, can increase under drought conditions because of the increased oxidative stress perceived. Similarly, Oh et al [37] revealed that drought stress and high temperatures can lead to increased amount of bioactive compounds which may serve as the main defense mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Faktor lingkungan, yakni radiasi sinar matahari diperlukan dalam sintesis karotenoid (karotenogenesis) karena kemampuannya untuk menyerap cahaya. Selain itu, pupuk K, jenis tanah, ketinggian tempat, suhu, ketersediaan air, musim, umur panen, dan ukuran umbi juga berpengaruh terhadap warna dan kadar beta karoten ubi jalar (Liu et al 2009;Ukom et al 2009;Abd El-baky et al 2010;Ukom et al 2011;Laurie et al 2012;Faber et al 2013;Motsa et al 2015;Kathabwalika et al 2016). pemberian pupuk rekomendasi urea, TSP, dan KCl masing-masing 100 kg/ha (Ginting et al 2013).…”
Section: Sifat Fisik Dan Kadar Beta Karoten Umbiunclassified
“…pemberian pupuk rekomendasi urea, TSP, dan KCl masing-masing 100 kg/ha (Ginting et al 2013). Pada kondisi lingkungan tumbuh yang kurang optimal, sisntesis metabolit sekunder, termasuk beta karoten, biasanya meningkat sebagai mekanisme pertahanan diri tanaman (Jaleel et al 2009;Wang dan Frei 2011;Motsa et al 2015). Namun hasil penelitian ini perlu dikonfirmasi lagi pada lokasi yang sama melihat besarnya variasi kadar beta karoten umbi (Tabel 2) dan relatif kecilnya ukuran umbi untuk memastikan pengaruh perlakuan pemupukan N terhadap kadar beta karoten ubi jalar di lahan pasang surut.…”
Section: Sifat Fisik Dan Kadar Beta Karoten Umbiunclassified
See 1 more Smart Citation
“…Sweet potatoes are food crops with wide ecological adaptability, drought-tolerant, often cultivated in the marginal soils under low agricultural input and are able to grow with limited water available for irrigation (Motsa et al, 2015a;Motsa et al, 2015b;Chipungu et al, 2018;Lestari et al, 2019). Sweet potato plantations can reduce soil erosion because of its vines' ability to cover the soil surface (Oshunsanya, 2016).…”
Section: Introductionmentioning
confidence: 99%